Use of Technology and Its Management Issues in Nepalese Industries and Businesses (Nepalese Journal of Management Research, 2021)
This paper presents some of the facts regarding the use of technology in Nepalese industries and businesses. This is a research of paper. It uses a set of questionnaires to collect the responses regarding technology management issues. It also reviews and describes scholarly papers, professional research works, and research reports of different national and international organizations to answer the research questions and draw results. Results show that Nepal is rich in many types of traditional technologies. Most of rural businesses are dependent on traditional technology for their activities. The contribution of traditional technology is still important in Nepal’s social-economic sphere and it cannot altogether be neglected. The results also show that the uses of modern technologies are also increasing in Nepal. Regarding modern technologies, information technology (IT), sophisticated technology, biotechnology and tissue culture technology, solar power, computer technology, automation, e-banking, mobile banking, locker facilities, telephone and television, and e-business become popular in Nepalese industries and businesses. The results reveal that lack of political commitment, lack of interactions, the gap between policies and practices, lack of coordination, lack of need assessment, low quality of practical education, low investment in research & development (R&D), inadequate maintenance facilities, the rapid pace of technological change, and non-involvement in decision-making are the key issues related to the management of technology in our context. The focus on R&D is essential for the development of new technologies in Nepal.